Evaluation of e-Sakip's Impact on Badung Regency's Local Government Performance - I Gusti Ngurah Agus Krisna Kusuma; Anak Agung Ngurah Eddy Supriyadinata Gorda (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study evaluates the implementation of e-SAKIP in the Badung Regency Government, identifies factors influencing its implementation, and examines its contribution to strengthening good governance in Bali, Indonesia.Research Methodology: A qualitative case study approach was used. Data were collected through interviews, observations, and document analysis and analyzed using the Context, Input, Process, and Product (CIPP) evaluation model and the Information Systems Success Model (ISSM).Results: The findings indicate that e-SAKIP improves transparency, reporting efficiency, and the integration of performance information across local government agencies. The key supporting factors include regulatory frameworks, leadership commitment, digital infrastructure, and institutional support. However, its utilization remains largely administrative and has not been fully optimized as a strategic decision-making tool. Challenges include limited human resource capacity, inconsistent data quality, weak inter-agency coordination, and compliance-oriented organizational culture.Conclusions: The implementation of e-SAKIP in Badung Regency strengthened administrative accountability and supported bureaucratic reform. Nevertheless, further improvements are needed to enhance outcome-based accountability and the strategic use of performance information in the governance process.Limitations: This study focused on a single local government context and applied a qualitative approach, limiting broader generalization.Contributions: This study enriches the literature on performance accountability, digital governance and bureaucratic reform in local government.